Hubungan Pemanfaatan Sistem Informasi Jejaring Rujukan Maternal dan Neonatal (Sijariemas) Dengan Upaya Stabilisasi Pasien Pra Rujukan Di RSUD Nganjuk - Naily Annisa Yonasri; Shinta Kristianti; Suwoyo Suwoyo (Akademi Keperawatan Dharma Husada Kediri, 2017)
Maternal and infant mortality rates reflect the magnitude of health problems and quality of health services in a community. One reason the referral system that does not have standard protocols in the referral network. This can be minimized if the SIJARIEMAS program is established, information system with the main function of emergency referral exchange communication and planned referral for neonatal maternal cases in the networked referral health facilities. The purpose study was to determine the correlation of utilization of Maternal and Neonatal Reference Network Information System (SIJARIEMAS) with stabilization efforts of pre-referral patients Nganjuk Regional Hospital. The design of this study was cross sectional. The sample of neonatal maternal referral cases was 127 references. Data collection taken by secondary data in the form of medical record data of patients on labour register, data server computer SIJARIEMAS, and data sheet of maternal neonatal reference. Data was analyzed by chi-square test (). The result of statistical test was 0.000 so there is correlation of utilization of Maternal and Neonatal Referral Network System (SIJARIEMAS) with patient pre-referral stabilization effort Nganjuk Regional Hospital. Therefore, the utilization of SIJARIEMAS in the referral process was recommended, so the form preparedness of emergency cases handling and implementation of stabilization before referral to improve patient condition.